2012
DOI: 10.1007/s10593-012-0940-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of 3-[(methyl)bis(5-trialkylsilyl-furan-2-yl)silyl]propylamines

Abstract: Novel 3- [(methyl)bis(5-trialkylsilylfuran-2-yl) silyl]propylamines have been synthesized by a hydrosilylation reaction of aliphatic and heterocyclic N-allylamines in the presence of the Speier's catalyst. The effects of the structure of the amine and the alkyl substituent at the silicon atom on the cytotoxicity of the compounds have been studied.Heterocyclic amines are important structural fragments in many medicinal preparations [1,2]. Analysis of antitumor substances has shown that the introduction of a het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[4] On the other hand, heterocyclic amines are important structural fragments in many medicinal preparations. [5,6] The analysis of antitumor substances has shown that the introduction of a heterocyclic amino group leads to an increase in the solubility and the bioavailability of the active substance.Our previous investigations have demonstrated [7][8][9] that 3-[dimethyl(5-trialkylsilyl(gemyl)furan-2-yl)silyl]propylamines and 3-[(methyl)bis(5-trialkylsilylfuran-2-yl)silyl]propylamines possess promising cytotoxic activity accompanied by high toxicity and cytotoxicity to normal cells. To improve the cycloselectivity of this class of compounds and to reduce their toxcicity we decided to prepare a novel series of furylpropylamines, which contain a silacycle and an organosilicon or -germanium substituent in the furan ring in a single molecule and to study the cytotoxicity of the obtained compounds and estimate the effect of the silacycle, nature of the amine, and the type of element-organic substituent on the cytotoxicity.The starting 2-substituted furylhydrosilane 1 was prepared from furan by reaction with butyllithium, followed by addition of 1-chlorosilinane, 2,5-substituted furylhydrosilanes 2-5 have been prepared from substituted furans in a similar way.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[4] On the other hand, heterocyclic amines are important structural fragments in many medicinal preparations. [5,6] The analysis of antitumor substances has shown that the introduction of a heterocyclic amino group leads to an increase in the solubility and the bioavailability of the active substance.Our previous investigations have demonstrated [7][8][9] that 3-[dimethyl(5-trialkylsilyl(gemyl)furan-2-yl)silyl]propylamines and 3-[(methyl)bis(5-trialkylsilylfuran-2-yl)silyl]propylamines possess promising cytotoxic activity accompanied by high toxicity and cytotoxicity to normal cells. To improve the cycloselectivity of this class of compounds and to reduce their toxcicity we decided to prepare a novel series of furylpropylamines, which contain a silacycle and an organosilicon or -germanium substituent in the furan ring in a single molecule and to study the cytotoxicity of the obtained compounds and estimate the effect of the silacycle, nature of the amine, and the type of element-organic substituent on the cytotoxicity.The starting 2-substituted furylhydrosilane 1 was prepared from furan by reaction with butyllithium, followed by addition of 1-chlorosilinane, 2,5-substituted furylhydrosilanes 2-5 have been prepared from substituted furans in a similar way.…”
mentioning
confidence: 99%
“…Synthesis of 1-{3-[1-(5-organylsilylfuran-2-yl)silinan-1-yl]propyl}amines and some trimethylgermyl analogues.ethylsilyl substituents, and this agrees well with the silicon shifts in 2-trimethylsilylfuran (d = À11.5 ppm) [10] and 2-triethylsilylfuran (d = À3.6 ppm). [9] The higher field signals at d = À13.4 to À13.8 ppm and at d = À30.7 to À31.1 ppm are due to the resonance of the silicon atom in the silacycle in the furylpropylaminosilinanes (compounds 6-24) and hydrosilanes (compounds 1-5), correspondingly (see Table 3 in the Supporting Information).The cytotoxicity of amines 6--24 in vitro was investigated on two cell tumor lines, namely HT-1080 (human fibrosarcoma) and MG-22A (mouse hepatoma), and normal mouse fibroblasts NIH 3T3 to determine the effect of silacyclization and the nature of the element-organic substituent in position 5 of the furan ring. Most of the studied compounds (9--22 and 24) exhibited high cytotoxic activity (IC 50 1-7 mg mL À1 ) in both cancer cells accompanied by high toxicity (LD 50 74-293 mg kg À1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations